The Impact of Emerging New Diagnostic Laboratory Techniques on Clinical Infectious Diseases - Vinall, Phil (MD Conference Express, 2012)
Along with a futuristic view, this article presents a technical and historical review of current diagnostic methods for infectious diseases. Topics focus on new testing methods, including nucleic acid sequencing, polymerase chain reaction, and mass spectrometry, and the effects of this technology on healthcare outcomes.